Quality of life and severity of tobacco dependence (Archives of Clinical Psychiatry, 2007)
BACKGROUND: Quality of life is a construct that has been increasing its importance as a means to access the impact, either of a given pathology or of a therapeutic strategy applied to a given subject. This parameter has been researched in the most various areas, among which, smoking. OBJECTIVE: Evaluating the association between quality of life and the severity of tobacco dependence. METHOD: A transversal study has been applied, using a convenience sample of 276 tobacco users, selected at random, tobacco-related diseases free. The instruments used were: World Health Organization Quality of Life Instrument (WHOQOL-BREF), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Fagerström Test for Nicotine Dependence and a social and demographic data file. RESULTS: It has been found association between the severity of tobacco dependence and the lowest scores in all domains of quality of life, evaluated by WHOQOL-BREF. Such result has been influenced by anxiety and depression symptoms. CONCLUSION: Heavy smokers have less quality of life but this group its also that with heavy depressive and anxiety symptoms, therefore, it is important that more studies are applied on the topic.